Eccentric hip adduction and abduction strength in elite soccer players and matched controls: a cross-sectional study. Issue 1 (22nd October 2009) - Thorborg, K; Couppé, C; Petersen, J; Magnusson, S P; Hölmich, P
Abstract : Background: Eccentric hip adduction and abduction strength plays an important role in the treatment and prevention of groin injuries in soccer players. Lower extremity strength deficits of less than 10% on the injured side, compared to the uninjured side, have been suggested as the clinical milestone before returning to sports following injury. Objective: To examine whether a side-to-side eccentric hip adduction or abduction strength symmetry can be assumed in non-injured soccer players and matched controls. Material and Methods: Nine elite soccer players 19.4 (1.5) years and nine recreational athletes 19.5 (2.0) years matched for sex, height and weight were included. Eccentric hip adduction and abduction strength of the dominant and non-dominant leg was tested for all the participants using an eccentric break test with a handheld dynamometer. Results: The dominant leg was 14% stronger than the non-dominant leg for hip adduction in the soccer players (p<0.05). No other side-to-side strength differences existed in soccer players or controls. In soccer players, hip abduction strength was 17–31% greater than controls for the dominant (p<0.05) and non-dominant leg (p<0.001). Conclusion: Eccentric hip adduction strength was greater in the dominant leg than in the non-dominant leg in soccer players, but not in matched controls. Eccentric hip abduction strength was greater in soccer players than matched controls, but soccer does not seem to induce a similar eccentric strength adaptation in the hip adductors.